Serum Prolactin Status in Primary Sub-Fertile Males with Azoospermia and Oligozoospermia (Journal of Enam Medical College, 2021)
Background: Fertility is adversely affected by negative feedback of prolactin on hypothalamic secretion of gonadotropin-releasing hormone (GnRH). Hyperprolactinemia inhibits the pulsatility of GnRH secretion and may cause secondary hypogonadism and results in spermatogenic arrest and impaired sperm motility. Besides, prolactin is also directly related to spermatogenesis and steroidogenesis.Objective: This study was designed to assess the serum prolactin status in primary sub-fertile males with azoospermia and oligozoospermia.Materials and Methods: This study was carried out at Armed Forces Institute of Pathology (AFIP), Dhaka Cantonment from January 2019 to December 2019 on 150 males. The study population included primary infertile males, 50 azoospermic and 50 oligozoospermic as cases and 50 age-matched normozoospermic males with proven fertility as control. Serum prolactin levels were estimated in fasting sera by electrochemiluminescence immunoassay in all the three groups. The reference value for serum prolactin was 4−18 ng/mL.Results: Mean age for normozoospermic fertile males, oligozoospermic and azoospermic infertile males were 30.73 ± 4.13 years, 31.46 ± 4.59 years and 32.34 ± 5.04 years respectively. Mean serum prolactin level in normozoospermic fertile males, oligozoospermic sub-fertile males and azoospermic sub-fertile males were 9.44 ± 3.46 ng/mL, 12.02 ± 11.78 ng/ mL, and 10.48 ± 4.55 ng/mL respectively with no significant variation (p>0.05). Serum prolactin was within the normal range (4−18 ng/mL) in all (100%) normozoospermic fertile males, 84% oligozoospermic males and 90% azoospermic males. Eight (16%) oligozoospermic cases and five (10%) azoospermic cases had hyperprolactinemia. Among the oligozoospermic cases with hyperprolactinemia, four (50%) had elevated prolactin with hypergonadotrophic state and four (50%) cases showed isolated prolactin elevation. All five (100%) azoospermic hyperprolactinemia cases were associated with hypergonadotrophic state.Conclusion: Serum prolactin estimation should be evaluated in primary sub-fertile males with azoospermia and oligozoospermia. Cases of hyperprolactinemia should also be evaluated for gonadotroph status.J Enam Med Col 2021; 11(2): 86-91